Design of a Web-Based Digital Guestbook Application Using Barcode Technology - Ismail, Isman; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The advancement of information technology has significantly influenced numerous sectors, including administrative systems in educational institutions such as Islamic boarding schools (pesantren). One persistent challenge in this environment is the reliance on manual guest registration, which often hampers efficiency and data accuracy. This study aims to design and develop a web-based digital guest book application incorporating barcode scanning technology at Pondok Pesantren Nur Khodijah 3 Tahsin wal Tahfidz. The goal is to streamline and improve the accuracy of guest recording processes. The system was developed using a structured methodology that includes requirement analysis, system design, implementation, testing, and maintenance. The platform is built on web technologies, using specific programming languages and database systems, and is equipped with a barcode scanning feature to expedite the guest check-in process. Testing results indicate that the developed application significantly reduces the time required for data entry and minimizes input errors. The barcode system also simplifies the retrieval and management of guest information, resulting in a more organized and systematic administrative workflow. Furthermore, data security and consistency are enhanced, as each guest is assigned a unique code automatically stored in the database. This system has proven to improve speed, accuracy, and documentation in guest management. In the future, it can be further enhanced by integrating features for reporting and analyzing visitor data to elevate the overall quality of administrative services within the pesantren.